Skin trauma rapidly induces thermoregulatory plexus hyperemia, while an increased nutritive papillary capillary function can be detected after 24 h. (22nd November 2021) - Wikslund, Liv Kristin; Amundsen, Vivian Shubira; Kvernebo, Anne Kari; Standal, Øyvind Krøvel‐Velle; Kvernebo, Knut
Abstract: Objective: Clinical assessments and laser Doppler perfusion measurements (LDPM) of skin microcirculation have limited value, as they fail to capture events regulated by local metabolic needs at a papillary capillary level. This study aimed to examine the ability of computer‐assisted video microscopy (CAVM) and diffuse reflectance spectroscopy (DRS) to assess skin nutritive perfusion—compared to LDPM. Methods: Healthy volunteers ( n = 10) were examined after (≈1 and ≈24 h) an incision (5 × 1 mm) on the forearm, at 0.1 mm (only with CAVM), 2−3 mm, and 30 mm from the trauma. Results: No changes were detected by CAVM after ≈1 h. After ≈24 h, 0−1 mm from the trauma, both CAVM parameters were increased: functional capillary density (capillary crossings/mm, 11.8 ± 1.4 vs. 7.3 ± 1.2, p < .01) and capillary flow velocities (CFV, %capillaries with brisk flow, 10 ± 6.8 vs. 1 ± 1, p < .01). At a distance of 2−3 mm, only CFV was increased (6.2 ± 6.1 vs. 1 ± 1, p < .05). DRS and LDPM measurements increased 2−3 mm from the trauma line in relation to baseline after both ≈1 and ≈24 h, that is, with DRS (%microvascular oxygen saturation): 45.8 ± 7.4% (baseline), 70.0 ± 12.5% (≈1 h), and 73.1 ± 10.4% (≈24 h), p < .01 and with LDPM (a.u.): 7.2 ± 2.5 (baseline), 28.3 ± 18.7 (≈1 h), and 45.9 ± 16.3 (≈24 h), p < .01. Conclusions: ≈24 h after skin trauma, an increased function of the nutritive papillary capillaries can be detected by CAVM.